DIFFERENCES IN FORMATIVE ASSESSMENT RESULTS OF BASIC PHYSICS 2 STUDENTS IN OFFLINE AND ONLINE LECTURES ON SPECIAL RELATIVITY THEORY MATERIAL - Juita, Dewi; M, Yusmaridi; Guchi, Rani Amelia; Supriyadi, Supriyadi; David, Andrew (Program Studi Pendidikan Fisika FKIP Universitas Jambi, 2024)
The research was motivated by the Galodo disaster that occurred in Tanah Datar district. This disaster has an impact on the implementation of basic physics 2 lectures at UIN Mahmud Yunus Batusangkar which must be carried out online using the Zoom application. The research was conducted on two different campuses, namely 2nd semester students at UIN Mahmud Yunus Batusangkar and UIN Imam Bonjol Padang. This study aims to determine whether there are differences in the results of formative assessments of students who conduct online and offline lectures by chatting with lecturers, teaching methods, and teaching media. This research was analyzed using a quantitative approach with a control group posttest only design. The instrument used is a formative question on special relativity material in essay form. The results of the study were analyzed using an independent sample t test which resulted in a 2 tailed sig value (0.269) > 0.05 which indicates that there is no difference in the results of students' basic physics formative assessment between students who conduct online and offline lectures on special relativity theory material. The average formative score of students is also not much different in both samples. The use of appropriate lecture methods, strategies, and media needs to be improved in basic physics 2 lectures.